Predictors of mental health difficulties and subjective wellbeing in adolescents: A longitudinal study - Suzet Tanya Lereya; Praveetha Patalay; Jessica Deighton (Wiley, 2022)
Abstract Background Mental health and subjective well‐being are of great interest in both health policy and research. There has been considerable debate regarding whether mental health difficulties and subjective wellbeing are two distinct domains or different ends of a single mental health spectrum. This study investigates if predictors of mental health difficulties and subjective wellbeing are the same or different in a large‐scale community‐based sample in the United Kingdom. Methods 13,500 adolescents in year 7 (aged 11-12) and again in year 8 (aged 12-13) completed surveys on emotional strengths and skills, support networks, mental health difficulties and wellbeing. Socio‐demographic factors were gathered from the National Pupil Database. Mental health difficulties and wellbeing scores were standardized to allow comparisons. Results The correlation between mental health difficulties and subjective wellbeing was −0.48, indicating a moderate overlap between the two domains. Some of the predictors (e.g., gender, ethnicity, problem solving, emotion regulation) in year 7 predicted both mental health difficulties and subjective wellbeing in year 8. However, some of the predictors in year 7 only predicted mental health difficulties (e.g., special education needs, empathy) and some only subjective wellbeing (e.g., prosocial behaviour, peer support) in year 8. Conclusion This study provides further evidence for differences in what predicts adolescents' mental health difficulties and subjective wellbeing. It highlights the importance of not only focusing on preventing or treating symptoms of mental illness but also focusing on improving children's wellbeing.